(3GdeSGFd GdbGSejIs - (3GdbGVi TeS GdOjf LYaQ Hf CMeO Hf YHO GdSdGe GdjeGfi GdRjOis
(3ChdgG (B:s
(3eSCdI , jGTjYI GdEeGe GdbGSe Hf EHQGgje Ydjg GdSGe , gd JLhRhf Cf jeJMf Gddg SHMGfg CMO ef YHGOg HTF ef GdBdGe hGdCSbGe s
(3BNQgG (B:s
(3hgd Pdc jLhR dUMGH Ojf ChPi Jbhi hjbjf ? Ef ai Pdc dPcQi ddPGcQjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdESdGejs